The relationship between the concepts of Sustainable and Responsible Investment (SRI) and Sustainable Development Goals (SDGs) / Dr. Muhammad Zarunnaim Wahab and Dr. Mohamad Hanif Abu Hassan - Wahab, Muhammad Zarunnaim; Abu Hassan, Mohamad Hanif (Universiti Teknologi MARA, Kedah, 2023)
Sustainable Development Goals (SDGs) and Sustainable and Responsible Investment (SRI) are terms often used interchangeably nowadays. Generally, in the context of the SDGs, the goals are a call to the global communities to end poverty, protect the environment, and ensure that everyone can live in peace and prosperity by 2030 via 17 targeted goals (United Nations-Development Programme, 2020). As for the SRI concept, the Securities Commission (2019), Martini (2021) and Sciarelli, et al.,(2021) refer to SRI as any investing method that considers personal and societal beliefs when making investment decisions. Specifically, SRI is an investment approach that emphasises on the combining of profit generation and environmental, social, and governance concerns, also known as ESG concerns.